Hepatic encephalopathy syndrome: current aspects of diagnosis and treatment - D. I. Trukhan (Медицинский совет, 2016)
Chronic liver diseases (CKD) are located on one of the first places on the incidence and are currently the fifth most common cause of mortality in many developed countries. One of the manifestations caused by hepatic insufficiency, hepatic encephalopathy is a syndrome which is a violation of the functions of the brain, which manifests a wide range of neurological or psychiatric disorders of subclinical changes to coma. This article examines current aspects of diagnosis and treatment of hepatic encephalopathy, taking into account the recommendations of the European Association for the Study of the Liver (EASL) and the American Association for the Study of Liver Diseases (AASLD).